The Impact of COVID-19 on Technologically Disadvantaged Students in Afghanistan - Khuram, Mohammad Ajmal (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
COVID-19 has forced educators, institutions, and their staff to switch from physical to remote education This study investigates the effect of the COVID-19 pandemic on the international education system, particularly in Afghanistan. Specifically, this paper explores how students in Afghanistan have been affected by the pandemic, and identifies and evaluates the challenges faced by the education system of Afghanistan due to the pandemic. Moreover, factors affecting the use of technology by students in Afghanistan are also analyzed. A quantitative research methodology was utilized by collecting responses from students through a questionnaire distributed online. All data collected were subjected to descriptive statistical analysis. Results revealed that technology has not benefited students very much, and the effects of COVID-19 have been extreme on them. Furthermore, insufficient time to learn new technologies has proven to be challenging for students. Developing technology requirements for students during COVID-19 may be an important element of adaptability to the pandemic. Moreover, it was found that Afghanistan already had poor internet and technology infrastructure before the pandemic, which further deteriorated during COVID-19, leading students to experience increasing internet disconnection and costs and decreased communication with teachers. Effective strategies to deal with these problems are discussed.